The impact of virtual reality on student engagement in the classroom–a critical review of the literature - Lin, Xiao Ping; Li, Bin Bin; Yao, Zhen Ning; Yang, Zhi; Zhang, Minshu (Frontiers in Psychology, 2024)
Objective: The purpose of this review is to identify the impact of virtual reality (VR) technology on student engagement, specifically cognitive engagement, behavioral engagement, and affective engagement. Methods: A comprehensive search of databases such as Google, Scopus, and Elsevier was conducted to identify English-language articles related to VR and classroom engagement for the period from 2014 to 2023. After systematic screening, 33 articles were finally reviewed. Results: The use of VR in the classroom is expected to improve student engagement and learning outcomes, and is particularly effective for students with learning disabilities. However, introducing VR into middle school education poses several challenges, including difficulties in the education system to keep up with VR developments, increased demands on students' digital literacy, and insufficient proficiency of teachers in using VR.To effectively utilize VR to increase student engagement, we advocate for educational policymakers to provide training and technical support to teachers to ensure that they can fully master and integrate VR to increase student engagement and instructional effectiveness.